Agroecology, organizations and confidence. The interventions of agronomist technicians in La Plata (Argentina) horticultural belt - Martínez, Darío Gabriel (2023)
In Argentina, the largest fresh vegetables production is located at La Plata horticultural belt. In recent years, there has been a considerable increase in the sector based on the labor of Bolivian migrant workers. Currently, producer and professional organizations from different government agencies promote an agroecological transition that modifies the conventional vegetable production. Between 2016-2018 the combination of the economic crisis and the adverse climatic storms led to the agroecological discourse being installed in the producer organizations. State´s technical professionals played an important role in this process, although they have been working for a long time in the region. Based on ethnographic interviews with agricultural technicians, we problematize their interventions. This article explores the work performed by state professionals, the knowledge circulation and the construction of links made with the producers. In this way, three areas of intervention of these technicians could be specified: the agroecological discourse as innovation, the organizational dimension and the affection network that builds confidence.